Combination Treatment With Inhibitors of ERK and Autophagy Enhances Antitumor Activity of Betulinic Acid in Non–small-Cell Lung Cancer In Vivo and In Vitro - Sun, Chao-Yue; Cao, Di; Ren, Qian-Nan; Zhang, Shan-Shan; Zhou, Ning-Ning; Mai, Shi-Juan; Feng, Bing; Wang, Hui-Yun (Frontiers in Pharmacology, 2021)
Aberrant activation of the Ras-ERK signaling pathway drives many important cancer phenotypes, and several inhibitors targeting such pathways are under investigation and/or approved by FDA as single- or multi-agent therapy for patients with melanoma and non-small cell lung cancer (NSCLC). Here, we show that betulinic acid (BA), a natural pentacyclic triterpenoid, inhibits cell proliferation, and induces apoptosis and protective autophagy in NSCLC cells. Thus, the cancer-cell-killing activity of BA is enhanced by autophagy inhibition. Mitogen-activated protein kinases (MAPKs), and especially ERK that facilitates cancer cell survival, are also activated by BA treatment. As such, in the presence of ERK inhibitors (ERKi), lung cancer cells are much more sensitive to BA. However, the dual treatment of BA and ERKi results in increased protective autophagy and AKT phosphorylation. Accordingly, inhibition of AKT has a highly synergistic anti-cancer effect with co-treatment of BA and ERKi. Notably, autophagy inhibition by hydroxychloroquine (HCQ) increases the response of lung cancer cells to BA in combination with ERKi. In vivo, the three-drug combination (BA, ERKi, HCQ), resulted in superior therapeutic efficacy than single- or dual treatments in xenograft mouse model. Thus, our study provides a combined therapy strategy that is a highly effective treatment for patients with NSCLC.